PEMODELAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI CUSTOMER RELATIONSHIP MANAGEMENT MENGGUNAKAN ENTERPRISE UNIFIED PROCESS - Mubarok, Ahmad; Tjahjadi, Djaja Sukma (Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2019)
The information technology has an important role in a company or agency to run its business process. It can help to optimize the business continuity as in the customer service process. In this case, the company needs an information system to manage the relationship between the customer and company applied into the concept of Customer Relationship Management (CRM). The initial stage in the development of information systems is to design architecture including: technology architecture, data architecture, and business process architecture. The Unified Process (UP) is a framework of the instantiated software process, both the Rational Unified Process (RUP) and Enterprise Unified Process (EUP). The information system architecture of CRM uses the Enterprise UP method. It is an enterprise architecture design that can be used as a reference to build a CRM-based system that can increase core value in service to customers. The results of this study are recommendations for information systems architecture models and methods used to achieve the strategic goals of the organization, especially in terms of customer service.